Multilocus Variable-Number Tandem-Repeat Analysis for Geno-typing of Escherichia coli Strains Isolated from Hospital Wastewate - Omid FARAHANI; Reza RANJBAR; Sahar HONARMAND JAHROMY; Bahareh ARABZADEH (Tehran University of Medical Sciences, 2020)
Background: Escherichia coli is one of the most frequent causes of many common bacterial infections. As a potential reservoir, hospital wastewater is considered for the dissemination of bacterial pathogens such as E. coli. Therefore, research on hospital waste's bacteria by low-cost, rapid and easy molecular typing methods such as multilocus variable-number tandem-repeat analysis (MLVA) can be helpful for the study of epidemics. Methods: E. coli strains were isolated from hospital wastewater sources in Tehran, Iran, over a 24-month sampling period (Jun 2014- Jun 2016) and identified by standard bacteriological methods. The diversity of repeated sequences of seven variable-number tandem-repeat (VNTR) loci was studied by MLVA method base on polymerase chain reaction (PCR). Results: Overall, 80 E. coli isolates were discriminated into 51 different genotypes. Analysis of the MLVA profiles using a minimum spanning tree (MST) algorithm showed two clonal complexes with 71 isolates and only nine isolates were stayed out of clonal complexes in the form of a singleton. High genotypic diversity was seen among E. coli strains isolated from hospital wastewaters; however, a large number of isolates showed a close genetic relationship. Conclusion: MLVA showed to be a rapid, inexpensive and useful tool for the analysis of the phylogenetic relationships between E. coli strains under the study.